2020
DOI: 10.1016/j.ijid.2020.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the corona virus pandemic: will a novel filtered eye mask help?

Abstract: Non-hermetically sealed eye protection does not fully protect the eyes from airborne particles. Hermetically sealed eye protection fully protects the eyes from particles, but tends to fog up, rendering it unusable. This study aimed to build and test a filtered eye mask (FEM) to protect the eyes from airborne particles, while being usable without excessive fog build up. Methods: The steps performed to build the FEM were described. A hermetically-sealed standard eye mask (SEM) and an FEM were examined at 1-minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…Human to human transmission occurs via droplets which come out of an infected person's mouth after sneezing and coughing as well as direct contact to infected person (Guo et al, 2020;Yuen et al, 2020;Cai et al, 2020). Eyes are also route of virus entry in the body (Yu et al, 2020;Douglas and Douglas, 2020). However, in a study it was seen that infected pregnant ladies of third trimester had delivered the normal children.…”
Section: Modes Of Transmissionmentioning
confidence: 99%
“…Human to human transmission occurs via droplets which come out of an infected person's mouth after sneezing and coughing as well as direct contact to infected person (Guo et al, 2020;Yuen et al, 2020;Cai et al, 2020). Eyes are also route of virus entry in the body (Yu et al, 2020;Douglas and Douglas, 2020). However, in a study it was seen that infected pregnant ladies of third trimester had delivered the normal children.…”
Section: Modes Of Transmissionmentioning
confidence: 99%
“…Among the simple methods to prevent fogging of the eyewear, a variety of methods including the application of surfactant liquid, converting the eyewear to a filtered eye mask by creating vents sealed with N95 mask cutting and use of anti-fog glasses or anti-fog coating have been described. 6 , 9 , 12 , 13 However, the actual effectiveness of these methods which perform the operative procedures remains unknown. We tested three inexpensive modifications on a disposable sealed poly-hydrocarbon based protective eyewear and found that the detergent-based liquid surfactant was effective in maintaining the workable vision for as long as 2 h. The PET material based anti-fog film although prevented fogging for long but failed to provide the workable vision required for a simulated surgical task.…”
Section: Discussionmentioning
confidence: 99%
“…The currently recommended protective eyewears to prevent the exposure of the eye to aerosol or airborne particles are hermetically sealed eyewears. 8,9 With no space for outer air circulation and increased perspiration of skin in a closed cavity, the risk of fogging increases. Additionally, with the recommended operating room conditions in COVID times, i.e, temperature between 24 and 30 C and humidity between 30 and 70%, and also with the orthopedic procedures requiring exertion, the perspiration increases, resulting in excessive fogging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discomfort caused by hydrocolloids can also be avoided by using a viscose peel agent. [37,38] Application of these strategies to the protective equipment of current COVID-19 frontline nurses can reduce their discomfort, thereby increasing their psychological health, and their abilities to tend to their patients.…”
Section: Reduce the Negative Effects Of Protective Equipmentmentioning
confidence: 99%